Transient lymphedema due to intense physical activity. - Garofalo, L.; Milano, A. (European Journal of Pediatric Dermatology, 2016)
In literature there are not cases similar to the current one while there are reports on lymphedema of the upper limbs due to surgery or radiation therapy for breast cancer (BC). There are guidelines advising women operated for BC against intense activity of the upper limb to avoid the risk of lymphedema (3), though it is known that muscle activity helps the lymph progression in the lymphatic system (1). McNeely et Al. (2) studied the problem in women survived BC who practiced rowing, comparing after strenuous exercise the circumference of the arm ipsilateral to BC with that of the contralateral healthy arm. The exercise caused obvious edema of the limb ipsilateral to the CM, but also of the contralateral one, remaining unchanged the difference between the circumferences of the two limbs. The actual report supports the transient edema activity of physical stress.